Effects of Self-Regulated Learning on Student’s Reading Literacy: Evidence From Shanghai - Qi, Xiang (Frontiers in Psychology, 2021)
Many empirical studies have been conducted to investigate self-regulated learning (SRL) in the Western countries. Less well investigated is the SRL in the Chinese Mainland students and how it affects their academic achievement. On the basis of PISA 2009, this paper is aimed at exploring the SRL of 15-year-old Shanghai students, as measured by cognitive strategy (elaboration and memorization), metacognition (metacognition in understanding and remembering, metacognition in summarizing, and control strategy), and motivational belief (enjoyment of reading). In the aspect of SRL nature, the results reveal that 15-year-old students in Shanghai use elaboration strategy frequently and seldom use memorization strategy, and that they have high metacognition in understanding, remembering, and summarizing but have low control strategy, and that their enjoyment of reading is relatively high. In the aspect of SRL’s consequence for reading literacy, findings from multilevel linear regression corroborate previous evidence from the Western countries about the effect of SRL on academic achievement. Specifically, elaboration strategy, metacognition in understanding and remembering, metacognition in summarizing, control strategy, and enjoyment of reading are conducive to students’ reading literacy, while memorization strategy exerts a significantly negative effect on reading literacy. The findings could be useful in helping us to gain a better understanding of Shanghai students’ SRL.